Development of a Paradigm for Applied Accounting Research: A Way of Coping with Subject-Matter Complexity. - Dilley, Steven C.; Hayes, Randall B.; Steinbart, Paul (The Accounting Review, 1983)
During the past decade the organizations responsible for regulating the form and content of accounting disclosures have become increasingly active. As a result of this activity, the authoritative pronouncements in accounting have become increasingly technical and intricate in nature. This has caused a problem for accounting education: it has become very difficult to cover all, or even most, of the pronouncements within the standard accounting curriculum. This paper examines the approach adopted in law schools, where this problem has existed for some time. The basic approach, a blend of general-principles courses with applied research courses, is found to be adaptable to accounting education. Specifically, this paper recommends that accounting education should include applied accounting research techniques in its curricula to provide students with the means of dealing with a detailed and cumbersome body of authoritative literature. The paper also provides a suggested research design for conducting applied accounting research.